High-frequency generation of large-cross-section pulsed electron beams - Gushenets V. I.; Koval N. N.; Kuznetsov D. L.; Mesyats G. A. Gennady Andreyevich; Novoselov Yu. N.; Uvarin V. V.; Schanin P. M. (1991, 1991)
В фонде НТБ ТПУ отсутствует